Emergence of team engagement under time pressure: role of team leader and team climate. Issue 3 (13th June 2017) - Sharma, Anshu; Bhatnagar, Jyotsna
Abstract : Purpose: This paper aims to identify the determinants of team engagement emerging as a collective team-level phenomenon under time pressure context. The paper particularly explores how teams working under time pressure conditions use their social resources to develop into highly engaged teams. Design/methodology/approach: The paper develops a conceptual framework along with related propositions by integrating diverse literature from the field of team processes, leadership and engagement. The arguments are theoretically embedded into the job demands-resources (JD-R) model to explain the emergence of team engagement under time pressure conditions. Findings: The suggested conceptual model based on the JD-R model reveal that teams working under time pressure conditions view it as a challenging job demand and, hence, use their social resources as a coping mechanism, thereby developing into highly engaged teams. However, the paper finds that for team engagement to emerge under time pressure, teams require two important determinants. These two main determinants are team leader engaging behaviors and team climate. Engaging team leader's behaviors include four sub-components: emotional agility, use of humor, efficient delegation and quality of feedback. Team climate constitute three sub-components: open communication, fun at work and compassion within the team. Only teams which have a strong team climate and team leaders' engaging behaviors tend to have high team engagement under time pressure contexts. Research limitations/implications: The paper offers implications for both HR and line managers in team-based organizations to promote factors that enhance team engagement, for teams to perform under time pressure situations. Originality/value: The paper identifies determinants of team engagement under time pressure context and further adds to the understanding of team processes by theoretically exploring how time pressure as a job demand can be channeled in a positive manner for promoting team engagement by using teams' social resources: team leader's engaging behaviors and team climate.